Pediatric Clinical Trials in Mainland China Over the Past Decade (From 2009 to 2020) - Wu, Wen-Wen; Ji, Xing; Wang, Hao; Chen, Feng; Ding, Qian; Zhang, Guan-dong; Li, Man; Wang, Shan-shan; Ni, Ming-ming; Liu, Qing-qing; Xu, Jing; Wang, Qian (Frontiers in Medicine, 2021)
In mainland China, there remains a shortage of pediatric drugs. The Chinese government has recently launched policies and incentives to encourage pediatric drug development and clinical trials. However, data on the characteristics or development trends of these trials are limited. In this review, we extracted source data from the Chinese Clinical Trials Registry and Information Transparency Platform and systematically reviewed the pediatric clinical trials conducted in mainland China from 2009–2020, providing data support to policy makers and industry stakeholders. We included 487 pediatric clinical trials. Over the past decade, the number of pediatric trials has increased, especially since 2016. The most common therapeutic areas were infectious diseases (n = 108, 22.2%), agents for preventive purpose (n = 99, 20.3%), and neurological and psychiatric diseases (n = 71, 14.6%). The number of clinical trials involving epilepsy (39, 10.1%), asthma (33, 8.5%), and influenza (24, 6.2%) were the highest. The distribution of leading institutions is unbalanced in mainland China, with most units in East China (34.0%) and few in Southwest China (6.9%). China has made progress in improving the research and development environment of pediatric drugs and increasing pediatric trials. However, a wide gap in pediatric drug development remains between China and the developed countries. The pharmaceutical industry in China has faced grim setbacks, including study duplication, a lack of innovation, and poor research design. Thus, we suggest that the Chinese government should adjust their policies to improve innovation and clinical design capacity, and optimize resource allocation between regions.